Mediation of Dynamic Innovation Capability on Digital Transformation and Employee Collaborative Innovation on Employee Performance - Rukani, Sisca Devi; Ratnasari, Siwi Dyah (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Human capital is a vital component within a company, playing a pivotal role in determining the organization's success in meeting its goals. The research question revolves around investigating whether there is an impact of Digital Transformation and Employee Collaborative Innovation on Employee Performance and whether Dynamic Innovation Capability mediates Digital Transformation and Employee Collaborative Innovation on Employee Performance. The study aimed to analyze the effect of digital transformation and Employee Collaborative Innovation on employee performance mediated by Dynamic Innovation Capability. Research using quantitative methods. The study focused on Bank XYZ employees located in Malang City, with a sample size of 137 employees. Data were collected through questionnaires distributed to each employee, and the responses obtained will be analyzed using Partial Least Squares (PLS). The results of the study stated that: Digital Transformation and Employee Collaborative Innovation on Dynamic Innovation Capability make a positive and meaningful impact. The results of Digital Transformation and Employee Collaborative Innovation on Employee Performance make a positive and meaningful impact, and Dynamic Innovation Capability on Employee Performance has a favorable and significant impact. The mediation relationship of Dynamic Innovation Capability can mediate Digital Transformation on Employee Performance, and the mediation relationship of Dynamic Innovation Capability can mediate Employee Collaborative Innovation on Employee Performance. The findings of this investigation show that technological advances and close relationships between employees can create a form of good working relationships with innovations from digital developments that improve the performance of employees.